"Helping you to pay us": rapport management in debt collection call centre encounters - Harrington, Leigh (De Gruyter, 2018)
This paper investigates the rapport management (Spencer-Oatey 2005) that collections agents at a UK-based utilities company call centre are expected to perform during debt collection telephone interactions. It does so by examining the rapport-relevant information communicated in the textual materials, including training manuals and call-scoring criteria, through which a prescribed debt collection style is disseminated and implemented. The analysis reveals that there are tensions in the rapport-concerns collectors must attend to when using the style. Collectors are instructed to perform potentially face-threatening behaviours in order to collect debt, whilst simultaneously engaging in linguistic behaviour that may be interpreted as face-enhancing and which functions to develop rapport with the debtor. It is suggested that the local deployment of this contradictory “helping you to pay us” philosophy is problematic on multiple levels and may give rise to relational tensions between collectors and debtors who have conflicting expectations about rapport management entitlements. In turn, this may contribute to a culture of sanctioned face-attacks in call centres (Archer and Jagodzinski 2015). Therefore, I suggest that call centres may need to loosen the syncedochical hold they have over their employees, thereby affording them the flexibility and volition to cope with the complex face demands, unpredictability and potential volatility of debt collection encounters.